Implementation of Citizenship Education Through Pancasila Values in Handling Casesbullying - Halimatus Sakdiyah (International Journal of Students Education, 2024)
This research aims to find out and analyze further about how role education citizenship through mark pancasila in overcoming cases of bullying committed by school children base. This study held with method review literature systematic, which where theory or base the discussion obtained based onresults from several sources such as journals, articles, and social media such as (internet, youtube, tiktok) which of course relate with problem which will solved. Like which we know that moment this behavior bullying lots happen specifically on child school. Bullying said as something form violence child which done by friend his age to athe “lower” child or “weaker” in order to gain an advantageor personal satisfaction. bullying behavior that often occurs in children school base that is shaped verbal, for example each other scoffed. Bybecause that, task teacher at school base expected can repair charactergood on student as well as can push on student in understand and canmaintaining ethics towards others, especially through the values of pancasila lots contains value humanity.